2013
DOI: 10.7567/jjap.52.076301
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Properties of a 4-MeV C+ Ion Beam Entering a Narrow Gap between Two Cylindrical Glass Surfaces

Abstract: To investigate the possibility of guiding a fast, heavy-ion beam with tilted curved surfaces, we study the transmission properties of a 4 MeV C+-ion beam passing through a narrow gap between a convex glass lens and concave glass lens. The ion-beam transmission of 42–59% obtained at the tilt angle θ= 3° is 20–30 times greater than that of 2% estimated from the cross section of the narrow gap between the two cylindrical lenses. The results of laser-beam-transmission experiments indicate that, even at θ= 3.4° whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…This nonuniformity of the number density is attributed to the asymmetric shape of the CGC. Similar asymmetric behaviors were also exhibited by the transmission probability as functions of the tilt angle 42) and observation angle 43) of the incidence of the 4 MeV-C + and -C 4+ ion beams into the CGC. Furthermore, the deflection to the positive x direction (Fig.…”
Section: Ion Fluence Counted From the Etch Pits On The Cr39 Sheetssupporting
confidence: 64%
See 2 more Smart Citations
“…This nonuniformity of the number density is attributed to the asymmetric shape of the CGC. Similar asymmetric behaviors were also exhibited by the transmission probability as functions of the tilt angle 42) and observation angle 43) of the incidence of the 4 MeV-C + and -C 4+ ion beams into the CGC. Furthermore, the deflection to the positive x direction (Fig.…”
Section: Ion Fluence Counted From the Etch Pits On The Cr39 Sheetssupporting
confidence: 64%
“…The details of the CGC are described elsewhere, 42,43) nonetheless, we have provided a brief explanation herein. The structure of the CGC is schematically shown in Fig.…”
Section: The Cgcmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the ion-surface interaction at the inner walls of capillaries, in a previous work, the transmission properties of 4 MeV C + ions entering a curved glass channel were experimentally investigated. 31) Because the glass channel is formed by a convex cylindrical glass lens facing a concave cylindrical glass lens, we can adjust its curvature, gap distance, and material conditions (e.g., electric conductivity, roughness, composition, and structure). One of the biggest advantages of this method is that it allows for a wide choice of inner-wall surfaces for systematic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, for |θ| > 3°with respect to the ion-beam axis, our previous study showed that ion scattering from the concave surface results in higher transmission than that from the convex surface. 31) The charge state of incident ions is an essential consideration for guiding keV HCIs. [1][2][3][4][5][6][7] Actually, Stolterfoht et al found a significant broadening of the angular profile of 3 keV Ne 7+ ions guided through nanocapillaries compared with 1 keV H 2 + ions, after a sufficiently large amount of charge was deposited on the surface.…”
Section: Introductionmentioning
confidence: 99%